Effect of electroacupuncture on restless legs syndrome (RLS) in hemodialysis patients: A protocol for systematic review and meta-analysis. Issue 50 (11th December 2020) - Chen, Jia-Ming; Chiu, Ping-Fang; Chang, Yu-Jun; Hsu, Po-Chi; Chang, Chia-Chu; Lo, Lun-Chien
Abstract: Background: Restless legs syndrome (RLS) is frequent in dialysis patients and occurs predominantly in its most severe forms. The aim of the present study was to evaluate the effects of electroacupuncture (EA) in hemodialysis patients with RLS by heart rate variability (HRV) monitor. Methods: One hundred twelve subjects who were hemodialysis patients with RLS will be divided into 2 groups: experimental and control. Each subject will receive the treatment relevant to their group 2 times a week for 4 weeks. After 4 weeks of treatment the subject will enter a 2-week washout period, after which the subjects will switch groups. Measurements will include HRV recordings, International Restless Legs Syndrome Rating Scale (IRLSRS) and Insomnia Severity Index (ISI). Result: The results of this study will systematically evaluate the effectiveness and safety of electoracupuncture intervention for hemodialysis patients with RLS. Discussion: This study is the first investigation to analyze the relationship between EA and the change of HRV by an objective monitor. If the findings of the current trial are positive, this study will also help support an effective, safe and cheap approach to clinical treatment of this challenging disorder, help foster improved understanding the relationship between autonomic nervous system and RLS, and ultimately contribute to elucidate the mechanisms of EA. Trial registration: ClinicalTrials.gov Identifier: NCT04356794; registration date: April 22, 2020.